2015
DOI: 10.1016/j.str.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes during Acid-Induced Activation of Influenza Hemagglutinin

Abstract: SUMMARY Influenza hemagglutinin (HA) mediates virus attachment to host cells and fusion of the viral and endosomal membranes during entry. While high-resolution structures are available for the pre-fusion HA ectodomain and the post-fusion HA2 subunit, the sequence of conformational changes during HA activation has eluded structural characterization. Here we apply hydrogen-deuterium exchange with mass spectrometry to examine changes in structural dynamics of the HA ectodomain at various stages of activation, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
99
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(115 citation statements)
references
References 56 publications
14
99
2
Order By: Relevance
“…A previous cryo-ET study of influenza virus at low pH found evidence that HA can adopt a conformation in which HA1 domains remain associated but the stem of the spike shows differences consistent with the fusion peptide subdomain of HA2 being released (25). Structural mass spectrometry studies from our lab also indicated that as the pH approaches 5.5, the fusion peptide and associated regions in the stem become significantly more dynamic, suggesting they may be at least transiently released, while the HA1-HA1 interface remains well-ordered (23). Based on those previously reported studies, it thus appears that HA can adopt a type of fusion peptide-primed state.…”
Section: Resultsmentioning
confidence: 65%
See 4 more Smart Citations
“…A previous cryo-ET study of influenza virus at low pH found evidence that HA can adopt a conformation in which HA1 domains remain associated but the stem of the spike shows differences consistent with the fusion peptide subdomain of HA2 being released (25). Structural mass spectrometry studies from our lab also indicated that as the pH approaches 5.5, the fusion peptide and associated regions in the stem become significantly more dynamic, suggesting they may be at least transiently released, while the HA1-HA1 interface remains well-ordered (23). Based on those previously reported studies, it thus appears that HA can adopt a type of fusion peptide-primed state.…”
Section: Resultsmentioning
confidence: 65%
“…For X31 influenza virus, this activity peaks as the pH approaches 5.0 (24). While in vitro fusion assays often employ an abrupt pH drop to 5.0 where fusion activity is high, during endocytosis the virus experiences stages of acidification (49), and priming of HA and virus takes place under more-elevated pH conditions found in early to maturing endosomes (8,23,24,31). We sought to determine whether the relative populations of the fusion contact types shifted as the pH was lowered toward more fusion-optimal conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations